Education and Language on Instagram: 1000 Influencers in Spain and Portugal - Domínguez Martín, Rosa; Novoa Fernández, Olivia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Today educating means using virtual platforms to eliminate space-time barriers, democratizing teaching and access to knowledge. Social media enhances dissemination and interactive learning in various areas. This research analyzes educational profiles, with a particular focus on those related to languages. This paper analyzes the 1,000 most influential profiles on Instagram under the education category —500 from Spain and 500 from Portugal. Additionally, the study compares the results of the sample from both countries, analyzes the findings, and explores their pedagogical implications.